The Evolution of Digital Trade: Understanding Opportunities and Risks in a Globalized Economy - Ying Yu (International Society of Philosophy and Cosmology, 2024)
As a new manifestation of traditional trade in the era of the digital economy, digital trade relies on the cross-border flow of data and information, while promoting global economic and trade growth, enhancing consumer welfare, and creating a new form of global employment; it is also faced with of several problems, such as unbalanced development of the main players, restriction of the cross-border flow of data, big differences in digital privacy protection, too broad a dispute settlement mechanism and imperfect intellectual property rights system. Given the above, we should overcome them one by one by increasing support for weak and small subjects, strengthening coordination and communication in all areas of trade, and emphasizing the construction of intellectual property rules, to build a harmonious, safe, and stable digital trade environment.